Functionalized NH2-MIL-125 (Ti)-based material as well as preparation method and application thereof

By performing imidazole group grafting and bromide coordination reaction on NH2-MIL-125(Ti), functionalized NH2-MIL-125(Ti)-based material is formed, which solves the problems of limited adsorption capacity, insufficient selectivity, and stability in precious metal recycling and reduction effects, and achieves efficient and highly selective precious metal recovery and reduction effects.

CN119859281AActive Publication Date: 2025-04-22SHIJIAZHUANG TIEDAO UNIV

Patent Information

Application Number
CN202510094586.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-21
Publication Date
2025-04-22
Estimated Expiration
2045-01-21

AI Technical Summary

Technical Problem

In the prior art, NH2-MIL-125 (Ti) has problems such as limited adsorption capacity, insufficient selectivity, and stability that needs to be improved in terms of precious metal recycling and reuse.

Method used

Functionalized NH2-MIL-125(Ti)-based material was formed by performing imidazol group grafting and bromide coordination reaction on NH2-MIL-125(Ti). Imidazole groups enrich the active sites on the surface of the material and form a strong coordination effect between lonely electrons and noble metal ions, improving adsorption selectivity. The introduction of bromide ions changes the electron cloud distribution on the material surface, enhancing the electrostatic attraction and ion exchange capabilities.

Benefits of technology

The adsorption selectivity and adsorption amount of precious metal ions are significantly improved, the structural stability of the material is enhanced, the adsorption process is ensured continuously and stably, and the precious metal ions are reduced through light irradiation, achieving efficient recovery of precious metals.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119859281A_ABST
    Figure CN119859281A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of material preparation, and particularly discloses a functionalized NH2-MIL-125 (Ti)-based material as well as a preparation method and application thereof. The preparation method comprises the following steps: firstly, under the action of an organic base catalyst, grafting an imidazole group to an amino group of NH2-MIL-125 (Ti) to obtain imidazole grafted NH2-MIL-125 (Ti); then, the imidazole modified NH2-MIL-125 (Ti) material and alkyl bromide are subjected to a coordination reaction, and the functionalized NH2-MIL-125 (Ti)-based material is obtained. The functionalized NH2-MIL-125 (Ti)-based material provided by the invention has the advantages of high adsorption capacity, high selectivity, high adsorption rate, high reduction efficiency, stable structure and the like in the aspect of adsorbing and reducing the noble metal, and a very potential solution is provided for recycling and reusing the noble metal.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of material preparation, and in particular to a functionalized NH2-MIL-125 (Ti)-based material and a preparation method and application thereof. Background Art

[0002] In today's society, precious metals are widely used in electronics, chemicals, jewelry, medical and many other fields due to their unique physical and chemical properties, such as high conductivity, chemical stability, and catalytic activity. However, the reserves of precious metals in nature are limited and unevenly distributed. Their mining and refining processes are not only costly, but also have serious negative impacts on the environment. With the large-scale generation of precious metal-containing waste such as electronic waste, precious metal recycling and reuse has become a key way to alleviate resource shortages and environmental pressures. Traditional precious metal recovery methods, such as chemical precipitation, ion exchange, and solvent extraction, have many limitations. For example, the chemical precipitation method has a low recovery rate and is prone to produce a large amount of waste residue; the ion exchange method has poor selectivity and is difficult to achieve efficient separation of multiple precious metals; the solvent extraction method requires the use of a large amount of volatile and toxic organic solvents, which poses safety hazards and environmental pollution risks.

[0003] As a new type of porous material, metal organic framework materials (MOFs) have shown great potential in the fields of gas storage, separation, catalysis, etc. in recent years. Among them, NH2-MIL-125 (Ti) provides a new idea for solving the problem of precious metal recycling and reuse due to its unique structure and rich amino functional groups. It has a large specific surface area and a regular pore structure, which is conducive to the adsorption and diffusion of precious metal ions. However, there are relatively few studies and applications on the recycling and reuse of precious metals by NH2-MIL-125 (Ti), and it has problems such as limited adsorption capacity, insufficient selectivity, and stability that needs to be improved. Therefore, the development of a functionalized NH2-MIL-125 (Ti) material that can efficiently and selectively recycle and reuse precious metals has important practical significance and broad application prospects. Summary of the invention

[0004] In view of the problems in the prior art of applying NH2-MIL-125(Ti) to the recovery and reuse of precious metals, such as limited adsorption capacity, insufficient selectivity, and stability to be improved, the present invention provides a functionalized NH2-MIL-125(Ti)-based material, a preparation method and an application thereof.

[0005] In order to solve the above technical problems, the technical solution provided by the present invention is:

[0006] In a first aspect, the present invention provides a method for preparing a functionalized NH2-MIL-125 (Ti)-based material, comprising the following steps:

[0007] Step a, dispersing NH2-MIL-125(Ti) in an organic solvent, adding an organic base catalyst and N,N-carbonyldiimidazole, and performing a grafting reaction to obtain an imidazole-modified NH2-MIL-125(Ti) material;

[0008] Step b: dispersing the imidazole-modified NH2-MIL-125(Ti) material in an organic solvent, adding bromoalkane, and performing coordination reaction to obtain a functionalized NH2-MIL-125(Ti)-based material.

[0009] Compared with the prior art, the preparation method of the functionalized NH2-MIL-125(Ti)-based material provided by the present invention firstly grafts the imidazole group onto the amino group of NH2-MIL-125(Ti) under the action of an organic base catalyst. The introduction of the imidazole group greatly enriches the active sites on the surface of the NH2-MIL-125(Ti) material. At the same time, the nitrogen atom on the imidazole ring has a lone pair of electrons, which can form a strong coordination effect with the noble metal ions, thereby significantly improving its adsorption selectivity for the noble metal ions. Moreover, this grafting reaction makes NH2-MIL-125( The structural stability of the Ti) material is enhanced. In a complex solution system containing precious metals, it can better maintain its own structure and is not prone to collapse or degradation, thereby ensuring the continuous and stable progress of the adsorption process. Furthermore, the imidazole-modified NH2-MIL-125(Ti) material undergoes a coordination reaction with bromoalkane to further functionalize the material. The introduction of bromide ions changes the electron cloud distribution on the surface of the material, making the material have a stronger electrostatic attraction to the precious metal ions. At the same time, the bromide ions can undergo ion exchange with the precious metal ions to be adsorbed, further improving the adsorption amount and adsorption rate of the precious metal ions.

[0010] The functionalized material prepared by the method of the present invention not only retains the original large specific surface area and regular pore structure of NH2-MIL-125 (Ti), provides more adsorption space for the adsorption of precious metal ions, and enables the material to load a large amount of precious metal ions. At the same time, its regular pore structure is also conducive to the diffusion and transmission of precious metal ions inside the material, thereby accelerating the adsorption rate. At the same time, the grafted imidazole groups and bromide ions can act as active sites to coordinate or exchange ions with the precious metal ions, thereby enhancing the material's adsorption capacity for precious metals. When the material after adsorption is placed under light, the imidazole groups promote the transfer and separation of electrons in the NH2-MIL-125 (Ti) material, thereby reducing the adsorbed precious metal ions to generate precious metal elements.

[0011] Furthermore, in step a and step b, the organic solvent is toluene.

[0012] Furthermore, in step a, the organic base catalyst is 1,8-diazabicycloundec-7-ene.

[0013] The preferred catalyst can promote the grafting reaction of NH2-MIL-125(Ti) and N,N-carbonyldiimidazole and increase the grafting rate of imidazole groups.

[0014] It should be noted that in step a, the organic base catalyst is slowly added to the reaction system, and after addition, the mixture is sealed and stirred at room temperature for 1.0 h to 1.5 h to fully activate the amino group in NH2-MIL-125(Ti) and promote the reaction between the amino group and the imidazole group.

[0015] Furthermore, in step b, the bromoalkane is bromobutyl.

[0016] Furthermore, in step a, the mass volume ratio of the NH2-MIL-125(Ti) to the organic solvent is (1.0-1.5) g: (20-30) mL.

[0017] Furthermore, in step a, the amount of the organic base catalyst added is 0.2% to 0.4% of the mass of NH2-MIL-125(Ti).

[0018] Furthermore, in step a, the amount of N,N-carbonyldiimidazole added is 0.02% to 0.04% of the mass of NH2-MIL-125(Ti).

[0019] Furthermore, in step a, the temperature of the grafting reaction is 20° C. to 40° C., and the time of the grafting reaction is 12 h to 15 h.

[0020] Furthermore, in step b, the mass volume ratio of the imidazole-modified NH2-MIL-125(Ti) material to the organic solvent is (1-1.5) g:(20-30) mL.

[0021] Furthermore, in step b, the mass ratio of the bromoalkane to the imidazole-modified NH2-MIL-125(Ti) material is (1-1.5):(0.25-0.5).

[0022] Furthermore, in step b, the temperature of the coordination reaction is 60° C. to 70° C., and the reaction time is 20 h to 24 h.

[0023] It should be noted that the NH2-MIL-125(Ti) described in the present invention can be a commercially available product, or can be prepared by conventional methods in the art.

[0024] Exemplarily, the preparation method of NH2-MIL-125(Ti) comprises the following steps:

[0025] 2-aminoterephthalic acid is dissolved in a mixed solution of N,N-dimethylformamide and methanol, isopropyl titanate is added, the mixture is mixed evenly, and a hydrothermal reaction is carried out at 140° C. to 160° C. to obtain NH2-MIL-125 (Ti).

[0026] In a second aspect, the present invention provides a functionalized NH2-MIL-125 (Ti)-based material prepared by any of the above-mentioned methods for preparing the functionalized NH2-MIL-125 (Ti)-based material.

[0027] The functionalized NH2-MIL-125 (Ti)-based material prepared by the present invention has abundant active sites and a specific spatial structure, and exhibits a high adsorption rate and a large adsorption capacity when adsorbing precious metals. In practical applications, even in a solution with a low concentration of precious metal ions, the precious metal ions can be quickly adsorbed onto the material, and a large amount of precious metal ions can be adsorbed, thereby improving the efficiency and economic benefits of precious metal recovery.

[0028] In a third aspect, the present invention provides the use of the above-mentioned functionalized NH2-MIL-125 (Ti) based material in the recovery of precious metals.

[0029] The functionalized NH2-MIL-125(Ti)-based material provided by the present invention has many advantages in the adsorption and reduction of precious metals, such as large adsorption capacity, high selectivity, fast adsorption rate, high reduction efficiency and stable structure, and provides a highly potential solution for the recovery and reuse of precious metals.

[0030] In a fourth aspect, the present invention provides a method for recovering precious metals, comprising the following steps:

[0031] The functionalized NH2-MIL-125 (Ti)-based material is added to a solution containing the precious metal to be recovered for adsorption. After the adsorption is completed, the solid and liquid are separated, and the separated solid is irradiated with light to obtain the recovered precious metal.

[0032] The present invention uses functionalized NH2-MIL-125 (Ti)-based materials to adsorb and recover precious metals in a solution. The adsorption process can quickly enrich the precious metal ions in the solution onto the material. After the adsorption is completed, the adsorbed precious metal ions can be effectively reduced to metal elements in situ by illumination, thereby realizing efficient recovery of precious metals. The Au (0) / functionalized NH2-MIL-125 (Ti) composite material formed after in-situ reduction also has excellent catalytic activity and can be applied to a variety of catalytic reactions, thus having important research value and application potential in the field of catalysis. The present invention not only realizes the recovery of expensive precious metals, but also provides a catalyst with excellent performance for the field of catalysis, meets the requirements of green chemistry and sustainable development, and has high practical value. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 X-ray diffraction patterns of the products of each step in Example 1, wherein (a) NH2-MIL-125(Ti), (b) IM-NH2-MIL-125(Ti), and (c) IMOFs catalyst;

[0034] Figure 2 The Fourier transform infrared spectra of the products in each step of Example 1 are shown in FIG.

[0035] Figure 3 The scanning electron microscope images of the products of each step in Example 1, wherein (a) NH2-MIL-125(Ti), (b) IM-NH2-MIL-125(Ti), (c) IMOFs catalyst;

[0036] Figure 4 This is a micro-area element quantitative analysis diagram of the IMOFs catalyst prepared in Example 1;

[0037] Figure 5 This is a comparison chart of the adsorption effect of the products of each step in Example 1 on chloroaurate ions;

[0038] Figure 6 This is a TEM image of the IMOFs catalyst after photocatalytic reduction of the precious metal in Example 1; wherein (b) is a partial enlarged image of the red circle position in (a);

[0039] Figure 7 The PXRD spectrum of the IMOFs catalyst in Example 1 before and after the end of illumination after adsorbing chloroaurate ions. DETAILED DESCRIPTION

[0040] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0041] In order to better illustrate the present invention, further examples are given below.

[0042] Example 1

[0043] This embodiment provides a method for preparing a functionalized NH2-MIL-125 (Ti)-based material, comprising the following steps:

[0044] Step a, measure 3 mL of methanol and 27 mL of N, N-dimethylformamide and add them to a beaker, stir evenly with a magnetic stirrer, weigh 0.408 g of 2-aminoterephthalic acid and add it to the above beaker, stir until completely dissolved, then add 0.465 μL of isopropyl titanate, mix evenly, transfer the mixed solution to a high-pressure reactor containing a polytetrafluoroethylene liner, place it in a 150° C. forced air oven to react for 24 hours, take it out and cool it naturally to room temperature, centrifuge and separate the precipitate, and wash it with N, N-dimethylformamide until the supernatant is colorless, then wash it with methanol 3 times, and dry the resulting solid in a 60° C. vacuum drying oven to constant weight to obtain NH2-MIL-125 (Ti);

[0045] Step b, measure 20 mL of toluene and add it to a beaker, weigh 1.0 g of the NH2-MIL-125 (Ti) powder prepared above and add it to the beaker, mix evenly, then weigh 3 mg of 1,8-diazabicycloundec-7-ene and slowly add it to the beaker, seal and stir at room temperature for 1.0 h, then add 0.357 mg of N,N-carbonyldiimidazole, stir at room temperature for 12 h, centrifuge and separate the solid, wash the obtained solid with toluene until the supernatant is colorless, and dry it in a vacuum drying oven at 60 ° C for 24 h to obtain NH2-MIL-125 (Ti) grafted with imidazole groups, recorded as IM-NH2-MIL-125 (Ti);

[0046] Step c, measure 20 mL of toluene and add it to a beaker, weigh 1.2 g of the IM-NH2-MIL-125 (Ti) powder prepared above and add it to the beaker, stir evenly, slowly add 282 μL of 1-bromobutane, stir at 0°C for 1 hour, then transfer to a 70°C oil bath to react for 24 hours, naturally cool to room temperature after the reaction, centrifuge to separate the solid, wash with toluene until the supernatant is colorless, and dry in a 60°C vacuum drying oven for 12 hours to obtain a functionalized NH2-MIL-125 (Ti)-based material, recorded as IMOFs.

[0047] Characterization

[0048] Figure 1 The XRD patterns of NH2-MIL-125(Ti), IM-NH2-MIL-125(Ti) and IMOFs samples prepared from step a to step c are shown in Figure 1, and the simulated XRD pattern of NH2-MIL-125(Ti) is used as a reference. It can be observed from the figure that the characteristic diffraction peaks of the obtained pure sample NH2-MIL-125(Ti) are highly consistent with the simulated XRD pattern of NH2-MIL-125(Ti), which is consistent with the position of the XRD pattern reported in previous literature, proving the successful preparation of NH2-MIL-125(Ti). It can also be clearly observed in the figure that with the addition of the imidazole functional group and the anion Br -As the grafting process progresses, the characteristic diffraction peak intensity of NH2-MIL-125(Ti) material gradually weakens, but the peak position remains unchanged without shifting. This indicates that during the modification process, the crystal structure of NH2-MIL-125(Ti) material has not changed significantly, which can be attributed to the grafting process of the imidazole functional group occurring on the amino site of the ligand.

[0049] Figure 2 FT-IR spectra of NH2-MIL-125(Ti), IM-NH2-MIL-125(Ti) and IMOFs samples prepared from step a to step c. For NH2-MIL-125(Ti), the peak at 3367 cm -1 and 3437cm -1 The peak at 1385 cm is attributed to the stretching vibrations of NH and OH, while the peak at 1385 cm -1 、1435cm -1 and 1540cm -1 The peak at 1624cm is mainly caused by the stretching vibration of the aromatic C in the organic ligand and the vibration of the carboxyl CO. -1 The peak at 400-800 cm is mainly caused by the amino functional groups in the organic ligands in the NH2-MIL-125(Ti) material. -1 The broad peak of the band is caused by the vibration of Ti-O-Ti clusters in NH2-MIL-125(Ti) material. In IM-NH2-MIL-125 material and IMOFs sample, the 1624cm -1 The characteristic peak at 100% disappears, which is mainly because the grafting process occurs at the amino site, destroying the infrared characteristics of the original amino functional group. - , and did not destroy the nodes in the MOFs material, thus maintaining the original unique framework structure of the MOFs material. The imidazole functional group contains many Lewis basic nitrogen atoms, which can act as coordination and guest interaction sites in the ionization modification of MOFs materials. FT-IR results show that the imidazole functional group exists in the IMOFs sample, which is related to Figure 1 The results of XRD are consistent.

[0050] Figure 3 SEM images of NH2-MIL-125(Ti), IM-NH2-MIL-125(Ti) and IMOFs samples prepared in steps a to c. Figure 3 (a) is a SEM image of the NH2-MIL-125(Ti) sample in Example 1. It can be seen from the figure that the sample presents a thick, round, three-dimensional structure with a smooth and uniform surface, an average diameter of about 700nm, and an average thickness of about 200nm. Figure 3It can be observed in (b) and (c) that the diameter and thickness of the IM-NH2-MIL-125 and IMOFs samples did not change significantly, and the surface smoothness did not change.

[0051] Figure 4 The quantitative analysis of the micro-area elements of the IMOFs sample prepared in this example shows that the content of Br element is about 16%, indicating that the NH2-MIL-125 (Ti) material has successfully grafted the imidazole functional group and achieved the imidazole alkylation process.

[0052] Adsorption performance test

[0053] The NH2-MIL-125(Ti), IM-NH2-MIL-125(Ti) and IMOFs prepared in steps a to c were subjected to an adsorption test of chloroaurate ions, and the specific steps were as follows:

[0054] Take 2mL of 58.86mM chloroauric acid solution, add water to prepare an aqueous solution with an initial concentration of 400mg / L, measure 100mL of the solution and place it in a photocatalytic beaker, weigh 20mg of the above dry sample and slowly add it to the photocatalytic beaker, and stir at room temperature to perform the adsorption test.

[0055] The entire adsorption test was carried out in the dark. Every 20 minutes, 4 mL of the sample was transferred with a dropper and placed in a centrifuge tube for centrifugation. After centrifugation twice, the supernatant was taken to test the absorbance of the chloroauric acid solution at 285 nm before and after adsorption. The results are as follows: Figure 5 The test results show that after 100 minutes of adsorption, the adsorption rate of chloroauric acid by NH2-MIL-125(Ti) is 79%, the adsorption rate of chloroauric acid by IM-NH2-MIL-125(Ti) is 82%, and the adsorption rate of chloroauric acid by IMOFs is 90.7%.

[0056] The sample after the adsorption experiment was placed under a xenon lamp simulating sunlight for 6 hours. After the irradiation, the solid was separated by centrifugation and washed with deionized water until the supernatant was clear. The sample was dried in a vacuum drying oven to a constant weight to obtain a reduced sample. The HRTEM image of the sample is shown in Figure 1. Figure 6 As shown in the figure, it can be seen that the interplanar spacing of the sample is 0.234nm, which corresponds to the interplanar spacing of the Au (111) crystal plane, proving that Au nanoparticles are obviously present inside the material.

[0057] Figure 7 The PXRD patterns of IMOFs catalyst before and after irradiation after adsorption of chloroauric acid. From the figure, we can see that two strong diffraction peaks belonging to Au can be observed at 38.2° and 44.6°, corresponding to the (111) and (200) crystal planes of Au, respectively, indicating that the reduction of AuCl by imidazole and bromide ions4- The ions form metal Au nanoparticles. The characteristic peak of Au in the sample is significantly enhanced after illumination, indicating that more gold elements are formed under the action of photocatalysis, confirming that the material has the ability to photocatalytically reduce gold ions.

[0058] The IMOFs prepared above were subjected to an adsorption test of chloropalladate ions, and the specific steps were as follows:

[0059] Take 2 mL of 58.86 mM sodium chloropalladate solution, add water to prepare an aqueous solution with an initial concentration of 400 mg / L, measure 100 mL of the solution and place it in a photocatalytic beaker, weigh 20 mg of the dried IMOFs sample and slowly add it to the photocatalytic beaker, and stir at room temperature to perform an adsorption test.

[0060] The entire adsorption test was carried out in the dark. Every 20 minutes, 4 mL of the sample was transferred with a dropper and placed in a centrifuge tube for centrifugation. After centrifugation twice, the supernatant was taken to test the absorbance of the sodium chloropalladate solution at 420 nm before and after adsorption. The test results showed that after 100 minutes of adsorption, the adsorption rate of IMOFs on sodium chloropalladate was 81.7%.

[0061] Example 2

[0062] This embodiment provides a method for preparing a functionalized NH2-MIL-125 (Ti)-based material, comprising the following steps:

[0063] Step a, measure 4 mL of methanol and 26 mL of N, N-dimethylformamide and add them to a beaker, stir evenly with a magnetic stirrer, weigh 0.35 g of 2-aminoterephthalic acid and add it to the above beaker, stir until completely dissolved, then add 0.465 μL of isopropyl titanate, mix evenly, transfer the mixed solution to a high-pressure reactor containing a polytetrafluoroethylene liner, place it in a 150° C. forced air oven to react for 24 hours, take it out and cool it naturally to room temperature, centrifuge and separate the precipitate, and wash it with N, N-dimethylformamide until the supernatant is colorless, then wash it with methanol 3 times, and dry the resulting solid in a 60° C. vacuum drying oven to constant weight to obtain NH2-MIL-125 (Ti);

[0064] Step b, measure 25 mL of toluene and add it to a beaker, weigh 1.2 g of the NH2-MIL-125 (Ti) powder prepared above and add it to the beaker, mix evenly, then weigh 4.8 mg of 1,8-diazabicycloundec-7-ene and slowly add it to the beaker, seal and stir at room temperature for 1.0 h, then add 0.24 mg of N,N-carbonyldiimidazole, stir and react at room temperature for 15 h, centrifuge and separate the solid, wash the obtained solid with toluene until the supernatant is colorless, and dry it in a vacuum drying oven at 60 ° C for 24 h to obtain NH2-MIL-125 (Ti) grafted with imidazole groups, recorded as IM-NH2-MIL-125 (Ti);

[0065] Step c, measure 20 mL of toluene and add it to a beaker, weigh 1 g of the IM-NH2-MIL-125 (Ti) powder prepared above and add it to the beaker, stir evenly, slowly add 300 μL of 1-bromobutane, stir at 0°C for 1 hour, then transfer to a 60°C oil bath to react for 24 hours, naturally cool to room temperature after the reaction, centrifuge to separate the solid, wash with toluene until the supernatant is colorless, and dry in a 60°C vacuum drying oven for 12 hours to obtain a functionalized NH2-MIL-125 (Ti)-based material, recorded as IMOFs.

[0066] The NH2-MIL-125(Ti), IM-NH2-MIL-125(Ti) and IMOFs prepared in steps a to c were subjected to an adsorption test of chloroaurate ions, and the specific steps were as follows:

[0067] Take 2mL of 58.86mM chloroauric acid solution, add water to prepare an aqueous solution with an initial concentration of 400mg / L, measure 100mL of the solution and place it in a photocatalytic beaker, weigh 20mg of the above dry sample and slowly add it to the photocatalytic beaker, and stir at room temperature to perform the adsorption test.

[0068] The entire adsorption test was carried out in the dark. Every 20 minutes, 4 mL of the sample was transferred with a dropper and placed in a centrifuge tube for centrifugation. After centrifugation twice, the supernatant was taken to test the absorbance of the chloroauric acid solution at 285 nm before and after adsorption. The results are as follows: Figure 5 The test results show that after 100 minutes of adsorption, the adsorption rate of chloroauric acid by NH2-MIL-125(Ti) is 79%, the adsorption rate of chloroauric acid by IM-NH2-MIL-125(Ti) is 82%, and the adsorption rate of chloroauric acid by IMOFs is 90.3%.

[0069] Example 3

[0070] This embodiment provides a method for preparing a functionalized NH2-MIL-125 (Ti)-based material, comprising the following steps:

[0071] Step a, measure 3 mL of methanol and 30 mL of N, N-dimethylformamide and add them to a beaker, stir evenly with a magnetic stirrer, weigh 0.38 g of 2-aminoterephthalic acid and add it to the above beaker, stir until completely dissolved, then add 0.465 μL of isopropyl titanate, mix evenly, transfer the mixed solution to a high-pressure reactor lined with polytetrafluoroethylene, place it in a 150° C. blast oven to react for 24 hours, take it out and cool it naturally to room temperature, centrifuge and separate the precipitate, and wash it with N, N-dimethylformamide until the supernatant is colorless, then wash it with methanol 3 times, and dry the resulting solid in a 60° C. vacuum drying oven to constant weight to obtain NH2-MIL-125 (Ti);

[0072] Step b, measure 30 mL of toluene and add it to a beaker, weigh 1.5 g of the NH2-MIL-125 (Ti) powder prepared above and add it to the beaker, mix evenly, then weigh 3 mg of 1,8-diazabicycloundec-7-ene and slowly add it to the beaker, seal and stir at room temperature for 1.0 h, then add 0.6 mg of N,N-carbonyldiimidazole, stir and react at room temperature for 13 h, centrifuge and separate the solid, wash the obtained solid with toluene until the supernatant is colorless, and dry it in a vacuum drying oven at 60 ° C for 24 h to obtain NH2-MIL-125 (Ti) grafted with imidazole groups, recorded as IM-NH2-MIL-125 (Ti);

[0073] Step c, measure 30 mL of toluene and add it to a beaker, weigh 1.5 g of the IM-NH2-MIL-125 (Ti) powder prepared above and add it to the beaker, stir evenly, slowly add 400 μL of 1-bromobutane, stir at 0°C for 1 hour, then transfer to a 70°C oil bath to react for 20 hours, naturally cool to room temperature after the reaction, centrifuge to separate the solid, wash with toluene until the supernatant is colorless, and dry in a 60°C vacuum drying oven for 12 hours to obtain a functionalized NH2-MIL-125 (Ti)-based material, recorded as IMOFs.

[0074] The NH2-MIL-125(Ti), IM-NH2-MIL-125(Ti) and IMOFs prepared in steps a to c were subjected to an adsorption test of chloroaurate ions, and the specific steps were as follows:

[0075] Take 2mL of 58.86mM chloroauric acid solution, add water to prepare an aqueous solution with an initial concentration of 400mg / L, measure 100mL of the solution and place it in a photocatalytic beaker, weigh 20mg of the above dry sample and slowly add it to the photocatalytic beaker, and stir at room temperature to perform the adsorption test.

[0076] The entire adsorption test was carried out in the dark. Every 20 minutes, 4 mL of the sample was transferred with a dropper and placed in a centrifuge tube for centrifugation. After centrifugation twice, the supernatant was taken to test the absorbance of the chloroauric acid solution at 285 nm before and after adsorption. The results are as follows: Figure 5 The test results show that after 100 minutes of adsorption, the adsorption rate of chloroauric acid by NH2-MIL-125(Ti) is 79%, the adsorption rate of chloroauric acid by IM-NH2-MIL-125(Ti) is 82%, and the adsorption rate of chloroauric acid by IMOFs is 90.5%.

[0077] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modification, equivalent substitution or improvement made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a functionalized NH2-MIL-125 (Ti)-based material, characterized in that: The steps include: Step a, dispersing NH2-MIL-125(Ti) in an organic solvent, adding an organic base catalyst and N,N-carbonyldiimidazole, and performing a grafting reaction to obtain an imidazole-modified NH2-MIL-125(Ti) material; Step b: dispersing the imidazole-modified NH2-MIL-125(Ti) material in an organic solvent, adding bromoalkane, and performing coordination reaction to obtain a functionalized NH2-MIL-125(Ti)-based material.

2. The method for preparing the functionalized NH2-MIL-125(Ti)-based material according to claim 1, characterized in that: In step a and step b, the organic solvent is toluene; and / or In step a, the organic base catalyst is 1,8-diazabicycloundec-7-ene; and / or In step b, the bromoalkane is bromobutyl.

3. The method for preparing the functionalized NH2-MIL-125(Ti)-based material according to claim 1, characterized in that: In step a, the mass volume ratio of NH2-MIL-125(Ti) to the organic solvent is (1.0-1.5) g: (20-30) mL; and / or In step a, the amount of the organic base catalyst added is 0.2% to 0.4% by mass of NH2-MIL-125(Ti); and / or; In step a, the amount of N,N-carbonyldiimidazole added is 0.02% to 0.04% of the mass of NH2-MIL-125(Ti).

4. The method for preparing the functionalized NH2-MIL-125(Ti)-based material according to claim 1, characterized in that: In step a, the temperature of the grafting reaction is 20° C. to 40° C., and the time of the grafting reaction is 12 h to 15 h.

5. The method for preparing the functionalized NH2-MIL-125(Ti)-based material according to claim 1, characterized in that: In step b, the mass volume ratio of the imidazole-modified NH2-MIL-125(Ti) material to the organic solvent is (1-1.5) g: (20-30) mL; and / or In step b, the mass ratio of the bromoalkane to the imidazole-modified NH2-MIL-125(Ti) material is (1-1.5):(0.25-0.5).

6. The method for preparing the functionalized NH2-MIL-125(Ti)-based material according to claim 1, characterized in that: In step b, the temperature of the coordination reaction is 60° C. to 70° C., and the reaction time is 20 h to 24 h.

7. The method for preparing the functionalized NH2-MIL-125(Ti)-based material according to claim 1, characterized in that: The preparation method of NH2-MIL-125(Ti) comprises the following steps: 2-aminoterephthalic acid is dissolved in a mixed solution of N,N-dimethylformamide and methanol, isopropyl titanate is added, the mixture is mixed evenly, and a hydrothermal reaction is carried out at 140° C. to 160° C. to obtain NH2-MIL-125 (Ti).

8. A functionalized NH2-MIL-125(Ti)-based material, characterized in that: The functionalized NH2-MIL-125 (Ti)-based material is prepared by the preparation method of any one of claims 1 to 7.

9. Use of the functionalized NH2-MIL-125 (Ti) based material according to claim 8 in the recovery of precious metals.

10. A method for recovering precious metals, characterized in that: The steps include: The functionalized NH2-MIL-125 (Ti)-based material according to claim 8 is added to a solution containing the precious metal to be recovered for adsorption. After the adsorption is completed, the solid and liquid are separated, and the separated solid is irradiated with light to obtain the recovered precious metal.

Citation Information

Patent Citations

  • Alkali metal cation doping-based NH1-MIL-125 (Ti) material and preparation method thereof

    CN108404868A

  • MOFs material as well as preparation method and use thereof

    CN109316978A

  • Method for removing organic pollutants by using ionic liquid modified metal organic framework immobilized laccase

    CN115747195A

  • Method for preparing cyclic carbonate catalyst through carbon dioxide cycloaddition reaction

    CN117718079A

  • Method for synthesizing aryl oxazolidinone catalyst

    CN117718080A

Cited By

  • Ti-MOF-based nano material, preparation method thereof and application of Ti-MOF-based nano material in methylene blue dye adsorption

    CN120383738A